Innovative Application of Guangdong Chaoyang Paper Cutting Elements in Cheongsam Design - Hou, Kaihui; Sirinkraporn, Supavee (Asia Social Issues, 2023)
Cheongsam is usually made of brocade, satin, crepe, and silk. The patterns on the fabrics used are one of cheongsam design’s most essential fashion features. Therefore, the idea is to integrate a national intangible cultural heritage of Chaoyang paper-cutting folk art into cheongsam design, so as to inject some blood of local traditional culture into cheongsam and endow it with a different charm. This study proposes integrating two art forms, i.e., paper-cutting elements and cheongsam, to create a unique cultural and fashion product. Chaoyang paper cutting elements have been innovatively extracted and embedded in cheongsam clothing design through reading and querying the relevant materials. A proposed innovative mode of extracting and integrating the paper cutting elements, dubbed adaptive integration and mutual feature integration, respectively, ensured the creation of an aesthetically pleasing fashion good involving two distinct cultural elements. Four primary pattern arrangements have been presented namely: border design, all over pattern I &II and central placement. This is the first time a study proposed the integration of two prominent art forms to create a unique cultural and fashion product.